CCL2: An important cytokine in normal and pathological pregnancies: A review - Lin, Zhi; Shi, Jia-Lu; Chen, Min; Zheng, Zi-Meng; Li, Ming-Qing; Shao, Jun (Frontiers in Immunology, 2023)
C-C motif ligand 2 (CCL2), also known as monocytic chemotactic protein 1 (MCP-1), is an integral chemotactic factor which recruits macrophages for the immune response. Together with its receptors (e.g., CCR2, ACKR1, and ACKR2), they exert noticeable influences on various diseases of different systems. At the maternal-fetal interface, CCL2 is detected to be expressed in trophoblasts, decidual tissue, the myometrium, and others. Meanwhile, existing reports have determined a series of physiological regulators of CCL2, which functions in maintaining normal recruitment of immunocytes, tissue remodeling, and angiogenesis. However, abnormal levels of CCL2 have also been reported to be associated with adverse pregnancy outcomes such as spontaneous abortion, preeclampsia and preterm labor. In this review, we concentrate on CCL2 expression at the maternal-fetal interface, as well as its precise regulatory mechanisms and classic signaling pathways, to reveal the multidimensional aspects of CCL2 in pregnancy.